ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LEVERAGE PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015) - Lyna Yuliana; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2017)
This study is conducted to analyze the different factors that can determine leverage on manufacturing companies. Determinant factors of leverage are represented by size, generated resources, level of warrants, debt cost, growth opportunities, reputation and liquidity. This research refers to research conducted by Padron et al (2005) and Alipour et al (2015).The population of this study are all manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the periode 2013-2015 . Total Observation of 216 was determined by purposive sampling method. This study uses Ordinary Least Square (OLS) for hypotheses testing.The results show that size, generated resources, debt cost, and liquidity have a negative effect with statistical significance on leverage.Reputation has a positive effect with statistical significance on leverage. Level of warrants was not to have a significance effect on leverage, however it found that has a positive effect. Growth opportunities was not to have a significance effect on leverage, however it found that has a negative effect. The implication of this study showed that size, generated resources, debt cost, liquidity and growth opportunities can decrease leverage. However, reputation and level of warrants can increase leverage.